1997
DOI: 10.1111/j.2044-8295.1997.tb02656.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged use of coloured overlays for classroom reading

Abstract: Ninety-three children in a primary school and 59 children in two first-year classes of a secondary school were asked individually to observe a paragraph of random letters arranged to resemble text, and to compare the perceptual effects on its clarity of coloured plastic sheets overlaid on the text. A total of 29 colours were compared using 10 coloured plastic sheets and 19 pairwise combinations of sheets, one superimposed on another. The resulting colours sampled CIE 1976 hue angle (huv) and saturation (suv) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
151
0
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(165 citation statements)
references
References 13 publications
7
151
0
7
Order By: Relevance
“…Double overlays are used if symptoms remain (Wilkins, 2003). In six studies of normal unselected children in mainstream schools, about 20% used their chosen overlay long-term (Jeanes et al, 1997). Those that used their overlays read faster with them: 5% read more than 25% faster (Wilkins, 2002).…”
Section: Overlays Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Double overlays are used if symptoms remain (Wilkins, 2003). In six studies of normal unselected children in mainstream schools, about 20% used their chosen overlay long-term (Jeanes et al, 1997). Those that used their overlays read faster with them: 5% read more than 25% faster (Wilkins, 2002).…”
Section: Overlays Examinationmentioning
confidence: 99%
“…Reports of distortions are obviously subjective but they are associated with a measurable impairment of reading speed that can be measured objectively (Jeanes et al, 1997;Wilkins, , 2002Wilkins and Lewis, 1999;Wilkins et al, 1996Wilkins et al, , 2001) . In addition to direct evidence implicating pattern glare in the aetiology of visual stress (Evans et al, 1994(Evans et al, , 1996a, several studies have excluded other potential mechanisms (Evans et al, 1996a;Simmers et al, 2001a,b).…”
Section: Coloured Filtersmentioning
confidence: 99%
“…In another study the rate of reading test was carried out in five different conditions: without an overlay, with a clear (transparent) overlay, with the grey overlay from the intuitive overlays, and with two coloured overlays from the same set, one of the chosen colour and one of a colour opposite (complementary) to that chosen. Again rate of reading was only superior in the chosen colour overlay condition (Jeanes et al, 1997).…”
mentioning
confidence: 99%
“…When the individuals wear spectacles tinted with this colour, they have reduced symptoms such as eye-strain and headaches (Wilkins et al, 1996). Other studies have shown that coloured overlays eliminate symptoms and increase reading speed in these individuals (Irlen, 1991;Jeanes et al, 1997;Wilkins, 2003;Wilkins, Lewis, Smith, & Rowland, 2001).…”
mentioning
confidence: 99%
“…More recently, the e ect of this type of intervention on reading performance has been assessed using a new test of the rate of reading. This research shows that individually prescribed coloured ®lters can improve reading performance, as well as reducing the symptoms of asthenopia (Wilkins et al, 1996;Jeanes et al, 1997).…”
mentioning
confidence: 99%